110 Surgical bootcamps – the future of surgical training. (17th November 2016) - Bamford, Richard; Williams, S; Orchard, P; Rowlands, C; Boorman, T; Longman, R; Coulston, JE
Abstract : Introduction: Trainees progressing to a higher level of surgical training with increased responsibility can be a challenging time for trainees. Surgical Bootcamps are intensive, simulation rich environments that have been postulated to help reduce the impact of this transition point. We report the impact of a Surgical Bootcamp for General Surgery trainees. Method: All first year specialist trainees in general surgery attended a surgical bootcamp within the first week of starting their new rotations. The three-day programme exposed them to an induction to the region, interactive and simulation rich sessions related to technical and non-technical skills that included simulated Ward Rounds, Human Factors and cadaveric training. Trainees completed a pre and post course feedback with 5-point Likert scale and free text to assess the impact and value of the programme. Results: 24 trainees attended the bootcamp and 19 completed the feedback. Trainees identified simulated ward round, human factors training, breaking bad news, networking and understanding the legal aspects of consent as especially valuable. Significant improvements were identified in self-perceived confidence in non-technical skills (P < 0.001), technical skills (P < 0.001) and knowledge (p < 0.001). 17/19 (90%) trainees agreed that they were more prepared to work as a specialist trainee and 95% (18/19) agreed that the experience was enjoyable and would recommend it as a way of inducting further trainees to the region. Overall confidence in performing as a specialist trainee increased significantly as a result of the bootcamp (P < 0.001) Conclusion: Surgical Bootcamps offer a valuable and enjoyable process of inducting trainees to a region. The programme can have a positive impact on trainee's technical and non-technical skills and allows the development of professional relationships and collegiate support. Bootcamps should be considered as a training tool for inducting first year surgical trainees and as they progress to more senior levels of training.